Advances in the synthesis of bio-based aromatic polyesters: novel copolymers derived from vanillic acid and ε-caprolactone. Issue 34 (10th August 2016) - Gioia, C.; Banella, M. B.; Marchese, P.; Vannini, M.; Colonna, M.; Celli, A.
Abstract : A new and sustainable pathway for the synthesis of polyesters and copolyesters derived from vanillic acid is reported. The one-pot procedure does not require either solvents or purification steps. New bio-based crystalline copolymers with tunable thermal properties are obtained. Abstract : A new and sustainable pathway for the synthesis of polyesters and copolyesters derived from vanillic acid is suggested. The poor reactivity of the fenolic –OH group of vanillic acid has been overcome by etherification reactions with biobased ethylene carbonate: the full procedure towards poly(ethylene vanillate) (PEV) avoids solvents and purification steps and uses only bio-based reagents. The PEV thus obtained is an example of bio-based PET mimics, characterized by high thermal transitions and a notable level of crystallinity. However, probably due to its low molecular weight, the material is brittle. In order to solve such problems and to exploit the aromatic structure of PEV to enhance the properties of aliphatic polyesters, new copolymers based on PEV and poly-ε-caprolactone were prepared. The new materials are characterized by an EV crystalline phase and tunable thermal properties according to the composition.